auses, pathogenesis, clinical and anamnestic analysis and morphometric examination of respiratory distress syndrome and atelectasis in infants - Zebo I. Ruzieva (Zien Journals, 2025)
This article, compiled on the basis of an analysis of scientific literature, is devoted to the problem of respiratory distress syndrome and atelectasis in infants. Respiratory disorders are in 2nd place among diseases of infants, their overall incidence is 1% of all infants, and in premature infants it is up to 14%. The most common form of respiratory distress syndrome is atelectasis, the main causes of which are: weakness and slowing of the respiratory center, underdevelopment of the respiratory system, hypoxia or asphyxia, brain or spinal cord injury. Externally, the focus of atelectasis is fleshy, swollen, dark gray, microscopically the walls of the alveoli are tightly packed, the alveolocytes are displaced, and cells and hyaline membranes are found in the space
Keywords: infant; lung; breath; respiration